Magnitude effect in intertemporal allocation tasks - Chen Sun; Jan Potters (Experimental Economics, 2021)
Intertemporal choices are affected by both discount rate and utility curvature. We investigate how the two aspects of time preference are affected by the size of the total budget using an intertemporal allocation task. At the aggregate level as well as at the individual level, we find magnitude effects both on the discount rate and on intertemporal substitutability (i.e., utility curvature). Individuals are more patient when dealing with larger budgets and also regard larger budgets to be more fungible. The latter effect suggests that the degree of asset integration is increasing in the stake.
Keywords: C91; D12; D91; 330; Time preference; Magnitude effect; Convex Time Budget method; Asset integration